International Editorial Board of vol. 29 No. 1 (2025): Journal Scientific and Applied Research: International Editorial Board of vol. 29 No. 1 (2025): Journal Scientific and Applied Research - Boyanov, Petar (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2025)
International Editorial Board of vol. 29 No. 1 (2025): Journal Scientific and Applied Research